CompTIA Security+: SY0-601 certification guide complete coverage of the new CompTIA Security+ (SY0-601) exam to help you pass on the first attempt - Neil, Ian (Packt Publishing Ltd, 2020)
The CompTIA Security+ certification validates the fundamental knowledge required to perform core security functions and pursue a career in IT security. Authored by Ian Neil, a world-class CompTIA certification trainer, this book is a best-in-class study guide that fully covers the CompTIA Security+ 601 exam objectives. Complete with chapter review questions, realistic mock exams, and worked solutions, this guide will help you master the core concepts to pass the exam the first time you take it. With the help of relevant examples, you'll learn fundamental security concepts from certificates and encryption to identity and access management (IAM). As you progress, you'll delve into the important domains of the exam, including cloud security, threats, attacks and vulnerabilities, technologies and tools, architecture and design, risk management, cryptography, and public key infrastructure (PKI). You can access extra practice materials, including flashcards, performance-based questions, practical labs, mock exams, key terms glossary, and exam tips on the author's website at securityplus.training. By the end of this Security+ book, you'll have gained the knowledge and understanding to take the CompTIA exam with confidence.